Faktor-Faktor yang Berhubungan dengan Kejadian Kurang Energi Kronik (KEK) Pada Ibu Hamil di Wilayah Kerja Puskesmas Gardu Harapan Tahun 2024 - Febrika Usiyanti; Sari, Intan; Arie Anggraini; Putu Lusita Nati Indriani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Chronic Energy Deficiency (CED) is a condition where a pregnant mother experiences a chronic lack of food, resulting in health problems for the mother. The research aims to determine the factors related to the incidence of chronic energy deficiency (CED) in pregnant women in the working area of ​​the Gardu Harapan Community Health Center in 2024. This research design uses an analytical survey with a cross sectional method. The population in this study were all pregnant women in the working area of ​​the Gardu Harapan Community Health Center from January - December 2024. The sample in this study was all pregnant women in the third trimester who had their pregnancies checked at the Gardu Harapan Community Health Center when this research was conducted in May - June 2024. The analysis technique uses Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there is a partial relationship between age and the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the working area of ​​the Gardu Harapan Community Health Center in 2024, the p value = 0.000. There is a partial relationship between knowledge and the incidence of Chronic Energy Deficiency ( KEK) in pregnant women in the working area of ​​the Gardu Harapan Community Health Center in 2024 obtained a p value = 0.000. There is a relationship between family income and the incidence of Chronic Energy Deficiency (KEK) in third trimester pregnant women partially in the working area of ​​the Gardu Harapan Community Health Center in 2024 the value obtained p value = 0.000. It is hoped that the results of this research can be an illustration for the Gardu Harapan Community Health Center to further improve health services, especially services for checking the nutritional status of pregnant women in order to prevent incidents of Chronic Energy Deficiency (CED).